Amaryllis Lesion Nematode, Pratylenchus hippeastri Inserra et al., 2006 (Nematoda: Tylenchida: Pratylenchidae) - William T. Crow (EDIS)
Amaryllis lesion nematode is an important nematode pest of amaryllis in Florida. It reduces plant vigor, flower yield, and bulb size. As the nematodes tunnel through the root, the damaged cells die and collapse, forming lesions on the exterior and the interior of the root tissue. This 4-page fact sheet was written by William T. Crow and published by the UF Department of Entomology and Nematology, January 2013.